Between Destructiveness and Vitalism: Simmel’s Sociology of Crowds - Christian Borch (Conserveries Mémorielles)
This article studies Georg Simmel’s contribution to the sociology of crowds. The aim of the article is (1) to demonstrate the importance Simmel ascribed to the crowd topic, (2) to illustrate how his early view on crowds was inspired by the work of the major crowd theorists of his time, and (3) to reconstruct a vitalist image of crowds from Simmel’s later thought. The first part of the article portrays Simmel’s general perspective on the crowd as it appears in some of his key writings. The following parts are based on less familiar material, not least Simmel’s book reviews of Gustave Le Bon, Scipio Sighele, and Gabriel Tarde. Thus, the second part of the article analyzes Simmel’s discussions of Tarde and Le Bon. The third part demonstrates how Simmel’s explanation of destructive crowd behavior was inspired by his reading of Sighele’s work. Finally, the fourth part of the article examines the crowd in the light of Simmel’s essays on the metropolis and sociability. It is argued that this part of Simmel’s work allows for a vitalist interpretation of crowds, which differs greatly from what Le Bon, Sighele, and Tarde suggested, and which anticipates Elias Canetti’s theory of crowds.